The culture of play and the presence of mimese, deviance and repetition in childhood memories of migrants from SINOP-Mato Grosso (Olhar de Professor, 2020)
This paper proposes from childhood memories, in a historical-phenomenological perspective, to offer a reflection on the culture of play and the presence of mimesis, deviance and repetition in childhood games. These are implications constructed in a research conducted with narratives of memories’ migrants from Sinop, Mato Grosso state, who experienced their childhood in the colonization process of the city, especially between the years 1973 to 1986. The intention is to foster the discussion that independent of times and spaces, in the past and in the present, the children play, learn to play, invent, create and make playing the verb of their living and, thus, when they play, create their own worlds, their cultures children, are authors of their own histories. Finally, the work establishes a dialogue between the science and poetry of Manoel de Barros, since the literature of the poet contributes to a glance of childhood memories, as poiesis of life, as the arts of living.
Keywords: Memories. Childhood. Play.